Proton magnetic resonance spectroscopy as a diagnostic biomarker in mild cognitive impairment following stroke in acute phase. Issue 8 (25th May 2016) - Meng, Ningqin; Shi, Shengliang; Su, Ying
Abstract : To investigate proton magnetic resonance spectroscopy ( 1 HMRS) as a diagnostic biomarker to identify mild cognitive impairment (MCI) following stroke in the acute phase. A total of 72 stroke patients were recruited in the acute phase of stroke from the Department of Neurology, including 36 stroke patients with MCI and 36 stroke patients without MCI. All patients underwent brain MRI/MRS examination on a 3.0 T scanner and a neuropsychological test in the acute phase of stroke. Single-voxel 1 HMRS was performed to obtain hippocampal metabolism intensities and brain infarcts were assessed on MRI. Group difference in metabolite ratios was analyzed using a T -test. Spearman rank correlation was used to study the correlation between metabolite ratios and Montreal Cognitive Assessment scores. The hippocampal n-acetylaspartate/creatine (NAA/Cr) ratio was found to be significantly lower in stroke patients with MCI compared with stroke patients without MCI ( P <0.02). However, we found no differences in the metabolite ratios between hippocampus ipsilateral to infarctions and the contralateral side ( P >0.05) in stroke patients with MCI. Furthermore, a correlation was found between hippocampal NAA/Cr ratios and Montreal Cognitive Assessment scores in stroke patients with MCI ( P <0.01). 1 HMRS could be a biomarker to identify MCI following stroke in the acute phase by capturing neurodegenerative changes.